2016
DOI: 10.1111/bjh.14082
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis between RQ‐PCR and digital‐droplet‐PCR of immunoglobulin/T‐cell receptor gene rearrangements to monitor minimal residual disease in acute lymphoblastic leukaemia

Abstract: SummaryReal-time quantitative polymerase chain reaction (RQ-PCR) is a standardized tool for minimal residual disease (MRD) monitoring in acute lymphoblastic leukaemia (ALL). The applicability of this technology is limited by the need of a standard curve based on diagnostic DNA. The digital droplet PCR (ddPCR) technology has been recently applied to various medical fields, but its use in MRD monitoring is under investigation. In this study, we analysed 50 ALL cases by both methods in two phases: in the first, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 38 publications
3
42
1
Order By: Relevance
“…MRD detection by dPCR is still under investigation. From current studies, the sensitivity and accuracy of dPCR appear to be at least comparable to those of ASO RQ‐PCR (Drandi et al , ; Della Starza et al , ). Also, dPCR allows absolute quantification of the number of copies of the target DNA molecules, without a need for a standard curve constructed by serial dilutions of diagnostic DNA or plasmid DNA.…”
Section: Digital Pcrsupporting
confidence: 57%
“…MRD detection by dPCR is still under investigation. From current studies, the sensitivity and accuracy of dPCR appear to be at least comparable to those of ASO RQ‐PCR (Drandi et al , ; Della Starza et al , ). Also, dPCR allows absolute quantification of the number of copies of the target DNA molecules, without a need for a standard curve constructed by serial dilutions of diagnostic DNA or plasmid DNA.…”
Section: Digital Pcrsupporting
confidence: 57%
“…ddPCR reaches a sensitivity of less than 0.1%, as long as enough DNA input can be guaranteed, which is higher than the sensitivity of qPCR (around 0.5%) . Two studies have compared ddPCR to qPCR for minimal residual disease detection in peripheral blood and bone marrow aspirates of lymphomas and have shown comparable results with an advantage of ddPCR with regard to sensitivity …”
Section: Discussionmentioning
confidence: 99%
“…In this study, we present the newest generation of quantitative PCR, ie, droplet digital PCR (ddPCR). This technique is known for its superior sensitivity (<0.1%) compared with the currently used PCR strategies (0.5%–5%) …”
Section: Introductionmentioning
confidence: 99%
“…Recent evidences, as well as our experience, showed that MRD by NGS appears more specific for relapse prediction than MRD by RQ, reducing the proportion of false‐positive results.…”
Section: Discussionmentioning
confidence: 73%
“…Next‐generation sequencing (NGS) has also been shown to represent an excellent tool for MRD detection in precursor and mature B‐cell tumors . One important advantage of NGS compared with RQ‐based MRD assessment is that its quantitative discrimination is always superimposable to the sensitivity, while the RQ quantitative range is usually inferior to the sensitivity threshold.…”
Section: Discussionmentioning
confidence: 99%